Renouveaux théoriques dans la formation à distance : tentative de modélisation de l’hybridation - Jean Christophe Coquilhat (Syn-Thèses, 2015)
The object of this article is to try to renew the commonly accepted models in the field of open and distance learning. Technical evolutions and the vast array of new learning systems seem to beg for the creation of a unified model whose global structure could be sufficient to encompass distance learning in its various dimensions: temporality and learning pace, the two-fold dimension of learning objects, the roles of designers, tutors and learners, and the many filters comprised in the interfaces. For this purpose, it seems necessary to survey the theoretical fields dealing with distance learning, notably the pedagogical features of distance in itself, as well as the articulation between distance and absence. The proposed model is drawn from the transactional distance theory (the articulation between dialogue and content) and the theory of learner-context interaction (learning threads). The aim is to offer descriptors articulated around a pedagogical filter that includes all participants’ activities and roles mediated by hybrid systems.